Changes In Mangrove Land Area Using Landsat 8 Satellite Images In Blanakan Bay In 2018-2022 - Rahayu, Shafa Surya; Cahyadi, Ferry Dwi; Sasongko, Agung Setyo (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2025)
Mangrove forests in Subang Regency have experienced changes in area coverage due to the expansion of aquaculture ponds and coastal abrasion. This study aims to analyze the changes in mangrove area and density in Blanakan Bay, Subang Regency, during the period 2018–2022 using Landsat 8 satellite imagery. The method employed is a survey approach utilizing multispectral classification. The main assumption of this study is that changes in mangrove coverage can be observed through multitemporal satellite imagery that has undergone geometric and radiometric correction. The digitized Landsat images were overlaid to identify spatial changes in mangrove cover 2018-2022. Spatial analysis was conducted using Supervised Classification techniques and the Normalized Difference Vegetation Index (NDVI) to classify mangrove areas based on their density levels. The results showed that the mangrove area in 2018 was 553.2 hectares, which decreased to 384.2 hectares in 2022, indicating a reduction of 169 hectares.